Solving the Problem of Building a Labor Protection Management System in Small Enterprises Based on the Use of External Management - Albert ugli, Atabaev Kakhramon; Ivanovna, Petrosova Larisa; Madaminovna, Atabayeva Mamura (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the object of study is the OSH management system in small enterprises, the issues of the quality of organization and management of labor safety are considered, and the most vulnerable components of the current implementation of the OSH are identified. In order to improve the system, it is proposed to integrate the process of outsourcing the management of labor protection using the process of delegating a set of measures, taking into account the establishment of their expediency and effectiveness.